A genomics-based discovery pipeline for Pseudomonas derived antifungals effective against the wheat pathogen Zymoseptoria tritici - Lund, George (2023)
Zymoseptoria tritici, the causal agent of Septoria tritici blotch, is an economically important foliar fungal pathogen of wheat. Resistance to all known classes of fungicides has arisen over the last 30 years, and new chemical control strategies are urgently needed. Environmental bacterial isolates are a potential untapped source of naturally derived novel antifungal compounds effective against Z. tritici. Pseudomonas bacteria have shown great promise as a source of novel antifungal secondary metabolites, with a proven ability to antagonise many fungal plant pathogens both in in vitro and in planta settings. A high throughput screening methodology using the blastospore growth form of Z. tritici was used to screen a wheat-associated Pseudomonas collection containing 534 isolates. In total, 52 isolates were found to exhibit an antagonistic phenotype in vitro. A subset of 88 Pseudomonas isolates from the initial 534 isolates (17 antagonistic and 71 non-antagonistic) were genome sequenced and phylogenetically assigned to three Pseudomonas species groupings, namely P. koreensis, P. lurida and P. fluorescens, with each group possessing both antagonistic and non-antagonistic isolates. Furthermore, statistically significant differences in the mean sizes of zones of inhibition produced by antagonistic Pseudomonas isolates were found between genetically diverse Z. tritici isolates. Significant diversity in predicted secondary metabolite biosynthetic gene clusters (BGCs) was found from the genome assemblies of the Pseudomonas isolates. BGCs of the known antifungal compound 2,4-diacetylphloroglucinol (2,4-DAPG) was predicted from genome assemblies of 6 antagonistic Pseudomonas isolates, whilst 11 antagonistic Pseudomonas isolates were found to have no significant hit with known antifungal BGCs. 2,4-DAPG was found to be present in agar extracts of zones of inhibition produced by Pseudomonas isolate Roth 112 in the Z. tritici blastospore confrontation assay. An authentic chemical standard of 2,4-DAPG was also used to confirm antifungal activity against Z. tritici blastospores in vitro. Transcriptomic responses of predicted BGCs to confrontation with Z. tritici blastospores were found for both antagonistic and non-antagonistic Pseudomonas isolates. The highly significant (Padj < 0.01) upregulation of a currently unknown gene cluster was observed by antagonistic Pseudomonas isolate Roth 16, potentially encoding a yet uncharacterised siderophore. The findings of this study contribute to the understanding of Pseudomonas-Zymoseptoria interactions, and the potential of bio-prospecting to identify novel bacterial secondary metabolites implicated in fungal antagonism, which could ultimately lead to future crop protection products. More broadly, these combined approaches could be utilised to identify bacterial secondary metabolites with other functions.